Die Grenzen rechtsgeschäftlicher Leistungspflichten: zugleich ein Beitrag zur Korrekturbedürftigkeit der §§ 275, 311a, 313 BGB n.F. - Lobinger, Thomas (Tübinger rechtswissenschaftliche Abhandlungen, 2004)
Thomas Lobinger deals with issues that, under English law, are primarily subject to the »frustration of contract« doctrine. In this respect, he analyses important amendments to the BGB (German Civil Code) which were newly adopted by the so-called »Gesetz zur Modernisierung des Schuldrechts« (Contracts Modernisation Act). He argues that the only means of achieving a consistent application of these amendments is to interpret them as focusing attention on the intent and expectations of the contracting parties.